Mappanre Adek and Strengthening Social Bonds in Bulukumba Community, South Sulawesi: Living Qur’an and Anthropology Perspective - Basri, Halimah; Miswar, Andi; Amiruddin, Muhammad Majdy; Arsyad, Aisyah; Lahmuddin, Fakhruddin (El-Usrah: Jurnal Hukum Keluarga, 2025)
The Mappanre adek tradition is not only a traditional identity but also a religious identity practiced by the Bugis-Makassar community in Bulukumba, South Sulawesi. This study aims to discuss the strengthening of social ties through the Mappanre adek tradition from the perspective of the living Qur'an and anthropology. The article is important because it explains how Islamic values ​​are acculturated with traditional ceremonies among the Bulukumba community, South Sulawesi. This study uses an empirical legal method analyzed with the theory of Islamic legal anthropology. Data refers to the results of interviews and literature studies. Interviews were conducted to validate data on key informants, while literature refers to journal articles, books and research fields related to the focus of the discussion. The article concludes that it shows that traditional ceremonies, in addition to functioning as a glue for society, also contribute to the sustainability of social order through the integration of the community involved in the ceremony. This traditional ceremony exemplifies an attitude of mutual respect and sharing happiness. In addition, this traditional ceremony also structures social classes that almost never change. In the context of living Qur’an and anthropology, the tradition of mappaenre adek is an implementation of the values ​​of the Quran, such as ukhuwah Islamiyah, litaarafu, mutual respect practiced by the community. Tradition as custom contains beneficial values, namely maintaining social ties and social cohesion in society. So that the values ​​of the Quran and local culture are able to create a harmonious acculturation and accommodation